Skopje: Skopje Brutalism Trail: Rebuilding Social Fabric through Architecture and Performance - Mano Velevska, Marija; Velevski, Slobodan; Staničić, Aleksandar; Bajkovski, Blagoja; Dale, Holly (Writingplace, 2023)
The article reflects the city of Skopje from the perspective of the workshop Skopje Brutalist Trail held in late September 2022 as a part of the activities focused on fieldwork within the COST Action Writing Urban Places. The workshop departs from the general topics of brutalist architecture and solidarity, both highly relevant and related to the city and its culture. The idea of the workshop is to offer a new viewpoint by means of civic participation and activism in order to reassess forms of solidarity in the process of community building. The workshop engages creative writing and performing arts to develop urban narratives that link architectural legacy, in-situ findings and memories of people and places, juxtaposing past, present and future narratives.